Contesting education policy in the public sphere: Media debates over policies for the Queensland school curriculum - Thomas, Sue (Journal of education policy, 2002)
This paper investigates the work of media discourses on education policy in public debates over the Queensland school curriculum. It draws on theories of discourse ... to outline a conceptualization of policy and media texts as discourses in the public sphere. In so doing, it notes the significant contribution such public discourses on education make to the policy process. The paper employs critical discourse analysis to investigate the discursive constructions of curriculum during one particular policy initiative. The analysis focuses on newspaper debates over the inclusion of a subject called Health and Physical Education (HPE) in the Queensland secondary school curriculum. The paper shows how educational policy issues were discursively constituted and contested through the construction of public discourses on education policy. In particular, it demonstrates how such public discourses worked to construct authoritative voices on educational policy. (DIPF/Orig.)